The Church of Our Lady of Kazan Apse Mural Design and Its Sources - Gladkikh, Elena V. (Actual Problems of Theory and History of Art, 2022)
The Church of Our Lady of Kazan is one of the most notable examples of the revival that arose within the Russian religious architecture in the second half of the 19th century. The article is focused on the Kazan church apse mural, designed by the famous Moscow architect and restorer N. V. Nikitin in 1890. The church murals created during the age of Historicism in Russia have not yet been sufficiently investigated. N. V. Nikitin was the father of the archeological style in church paintings which arose in the late 19th – early 20th century. In this research, the medieval Christian monuments used by N. V. Nikitin as origin of the murals were uncovered from the archive documents. There is a great deal of importance attached to architect’s correspondence with Russian art historian and archaeologist P. P. Pokrovskii. These documents provide clarification and support for the redemption theme in Nikitin’s murals and other iconographic options expressed in his work. The value of the research is amplified by the loss of the Kazan church interiors in 1920 as well as the deconstruction of it in 1973.
Keywords: church of Our Lady of Kazan; church murals; N. V. Nikitin; N. V. Pokrovskii; Historicism; 19th-century Russian art